AN ANALYSIS OF THE MOTIVES UNDERLYING FOREIGN DIRECT INVESTMENTS (THE CASE OF GEORGIA) - CHARAIA, Vakhtang; LASHKHI, Mariam (CENTRAL ASIA AND THE CAUCASUS, 2018)
In general, Foreign Direct Investment (FDI) is considered a beneficial factor for local and international economic development. However, it is not always the case. Without taking into account the peculiarities of the local economy and MNE motivations, FDI could play a neutral, or in some cases even a negative role in the process of economic development, especially in developing countries with small markets. Historically, foreign investments have played a significant role in the economic growth of different countries by increasing local production and connecting the country to foreign markets. Georgia, as well as the whole world, has long recognized the positive impacts of FDI on its economy, especially for an import-dependent country with unstable/unreliable macroeconomic indicators and, moreover, with the ambition to become the regional economic hub. It is important to note that FDI has led to significant positive spillover effects on the labor productivity of domestic firms and on the rate of growth of domestic productivity.